Evaluating the Efficiency of the Fenton-Ultrasonic Process in Degradation of Trihalomethanes Precursors from Aqueous Environments Using Zero Iron by Response Surface Method - SA Sadat; A Pad; H Mari Oryad; G Hassani (Armaghane Danesh Bimonthly Journal, 2023)
Background & aim: The presence of natural organic substances (NOM) in aqueous solutions due to the creation of disinfection by-products (DBP) including trihalomethanes (THMs) and haloacetic acids (HAAs), as a result of the chlorination of aqueous solutions in the conventional purification process and according to Potential health risks for public health have attracted a lot of attention. Therefore, the aim of the present study was to determine and investigate the performance of combined Fenton-ultrasonic processes in removing the precursors of trihalomethanes from aqueous environments using zero iron.